“The Body Hair that Grows on the Head” - Donyol Dondrup; Charlene Makley (Ateliers d'Anthropologie)
In this chapter, we introduce readers to the Amdo Tibetan comedian, poet and performance artist Menla-kyap [sMan bla skyabs] through a translation of his 2009 autobiographical narrative, “Views on Hair and Hairstyles.” The Introduction section provides a broader context for Menla-kyap's life and times as well as a reading guide for this enigmatic piece. The translation is carefully annotated, yet attempts to stay as close as possible, formally and poetically, to the original text. Ultimately, we argue that the piece speaks not only to Menla-kyap's life but also to his critical views on all Tibetans' complex experiences of Chinese state rule since the 1960s.